FREVO AND MEDIA DANCES: SOME REFLECTIONS (Fiep Bulletin - online, 2011)
When studying frevo related to the dances of the cultural industry that are broadcasted on television to great population mass, it's interesting to understand how some historical events happened from both of expressions of dance. This article is characterized as a bibliographic and documental review, and it aims to describe and compare both kind of dances and reflect some of their aspects. For the review, articles, journals notices, academic texts from web and books were used. With the theoretical part it's possible to think about the cultural industry production that minimizes the popular expressions, and this is one of the reasons why the frevo is not explored the whole year. The media dances are absorbed by the people without questions or modifications about and it's important taking these reflections to the dance classes, where the creative process is fundamental not only in the frevo, but in the popular culture. Then, the students can be stimulated to think about the media information.
Keywords: Dance; Frevo; media dances